JINN IN THE THOUGHT OF MULLA SADRA - Bella Falina; Wa Ode Zainab Zilullah Toresano (Sadra International Institute, 2026)
This study examines the nature of jinn from the perspective of Mulla Sadra’s philosophy, one of the foremost figures of al-Ḥikmah al-Muta‘āliyyah (Transcendent Theosophy). The study is motivated by the fact that, although the existence of jinn is affirmed in the Qur’an and Hadith, rational arguments concerning their existence remain relatively limited within Islamic thought. This research aims to analyze the definition, existence, and characteristics of jinn according to Mulla Sadra. The study employs a qualitative method with a library research approach. Primary sources consist of Mulla Sadra’s works, particularly Mafātīḥ al-Ghayb, while secondary sources include journals, articles, and related studies. Data were analyzed using Paul Ricoeur’s hermeneutical method. According to Mulla Sadra, jinn are not merely imaginary beings but possess a genuine ontological reality. Through the concept of tashkīk al-wujūd (the gradation of existence), he explains that jinn occupy an intermediate position: subtler than corporeal human beings yet lower than angels, who are entirely imateriel. Jinn belong to the category of mumkin al-wujūd (contingent beings), whose existence is real and independent of human thought. In terms of their mode of existence, Sadra recognizes two forms of jinn. First, jinn as subtle aerial bodies capable of assuming various forms. Second, jinn as independent immaterial substances. Consequently, jinn possess both materiel and immaterial dimensions: elements of fire and air on the one hand, and a spiritual aspect beyond sensory perception on the other. This study is expected to contribute to the development of Islamic philosophical studies, particularly in the fields of theology and Qur’anic exegesis, and to serve as a reference for students and scholars interested in the philosophical study of unseen beings.